NOMS 2020 - 2020 IEEE/IFIP Network Operations and Management Symposium 2020
DOI: 10.1109/noms47738.2020.9110402
|View full text |Cite
|
Sign up to set email alerts
|

Automated optimal firewall orchestration and configuration in virtualized networks

Abstract: Emerging technologies such as Software-Defined Networking and Network Functions Virtualization are making the definition and configuration of network services more dynamic, thus making automatic approaches that can replace manual and error-prone tasks more feasible. In view of these considerations, this paper proposes a novel methodology to automatically compute the optimal allocation scheme and configuration of virtual firewalls within a user-defined network service graph subject to a corresponding set of sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Later, formal verification techniques have been exploited to provide correctness assurance after the automated computation of firewall configurations ( [12], [5], [17], [22], [1]). Then, after the advent of softwarization in networking, this research path has found new relevance ( [20], [8], [9], [6]) and currently has become an important research trend in network security.…”
Section: Related Workmentioning
confidence: 99%
“…Later, formal verification techniques have been exploited to provide correctness assurance after the automated computation of firewall configurations ( [12], [5], [17], [22], [1]). Then, after the advent of softwarization in networking, this research path has found new relevance ( [20], [8], [9], [6]) and currently has become an important research trend in network security.…”
Section: Related Workmentioning
confidence: 99%
“…The most significant frameworks for automatic configuration of packets filtering firewalls based on policy refinement are FIRMATO [4], FACE [25], MI-RAGE [9], and VEREFOO [7]. Moreover, a refinement model that allows the translation of high-level security requirements into low-level configuration settings for the virtual network security functions was introduced in [5].…”
Section: Policy Refinementmentioning
confidence: 99%
“…The first step is to understand which are the paths for a certain package to go from the source to the destination. For req 3 we have 1 // p is a policy rule 2 if configuration=="max" then Algorithm 2: Firewalls' population algorithm two paths: the first uses F w 1 7 and F w 3 and the second uses F w 2 ; for req 1 we have two paths: the first uses F w 1 and F w 3 and the second uses F w 2 ; and for req 4 we have two paths: the first uses F w 1 and the second uses F w 2 and F w 3 . req 3 should be applied in all paths, as it is an "allow " action, thus, it should be placed in all firewalls.…”
Section: Distribution Modulementioning
confidence: 99%
See 1 more Smart Citation
“…In light of these observations, the challenge we propose to face is to effectively exploit the benefits provided by the virtual networking paradigms, minimizing the impact of their beforehand illustrated drawbacks. With this aim, we designed a framework based on the innovative methodology presented in [8], based on Maximum Satisfiability Modulo Theories (MaxSMT), and we integrated it in the context of Kubernetes. The proposed approach automatically configures virtual firewalls, where a consistent number of configuration errors are traditionally performed.…”
Section: Introductionmentioning
confidence: 99%